(3ebGdI aj GdOZOZIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd Mfjf Hf ESMGb ai GdSHH GdPi dg EPG GeJOJ GdjO Ydi GdehGVY ef GdHOf hYQV ai Jdc GdehGVY hOZOZI ajchf eYgG VMc hHcGA eYkG s
(3BNQgG (B:s
(3hdPdc deG cGf gPG GdehVY ef GdbOejf jYQV dg GdOZOZI EPG eQJ GdjO Ydjg JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs